PERENCANAAN DINDING PENAHAN TANAH UNTUK PERBAIKAN LONGSOR DI RUAS JALAN BALEREJO KALEGEN - Lulut Fadhilah; Sudarno Sudarno (Universitas Tidar, 2017)
The road that connects Kalegen village and Balerejo village is the main road for Balerejo villagers, Kebonlegi villagers and Tanjungsari villagers. Besides the road is a cliff that has largely not been reinforced so that a landslide that is very dangerous for the road users. The landslide is 564cm in diameter and the cliff depth is 500cm. In order to prevent further damage and minimize the existing hazards, a retaining wall is required. The first is to look for soil data which includes the volume weight and the deep friction angle. After the ground data are collected then calculations are made to plan the design and dimensions of the retaining wall. Based on the analysis and calculation of retaining wall planned is Cantilever type with height 550 cm, width under 385 cm, width 55 cm, width of heel 130 cm, width of foot 100 cm, with retaining wall soil entering ground as high as 50 cm. The retaining wall of such type and dimension has been declared safe against the hazards of bolsters and the shear hazard based on the calculations already performed. Keyword: Landslide, retaining wall, Cantilever Wall